HISTORICAL ASPECTS OF THE VESICOURETERAL REFLUX STUDY AMONG CHILDREN - A.V. Ryabtseva; D.K. Fomin; S.P. Yatsyk; S.M. Sharkov; K.S. Abramov (Педиатрическая фармакология, 2008)
Vesicoureteral reflux is one of the most widely spread lower urinary tract diseases among children, which is the primary reason for the disturbed urodynamics and development of the chronic pyelonephritis. As a consequence, the contamination of the urinary tracts may be the reason for further development of the chronic kidney disease, renal hypertonia and may inevitably lead to disability. The modern diagnostics of the vesi coureteral reflux is very important for the adequate conservative and operative treatment. In the given article, the authors highlight the diagnostics development stages of this disease and provide comparative characteristics of different diagnostic methods.Key words: vesicoureteral reflux, urodynamics, diagnostics, children.